The association of baseline sarcoidosis measurements with 6-month outcomes that are of interest to patients: Results from the On-line Sarcoidosis Assessment Platform Study (OSAP). (May 2022) - Judson, Marc A.; Yucel, Recai; Preston, Sara; Chen, Edward S.; Culver, Daniel A.; Hamzeh, Nabeel; Lower, Elyse E.; Sweiss, Nadera J.; Valeyre, Dominique; Veltkamp, Marcel; Victorson, David E.; Beaumont, Jennifer L.; et al.
Abstract: Introduction: The impact of common measures to assess sarcoidosis have not been compared longitudinally to outcomes that are meaningful to patients. We prospectively examined the relationship of baseline measurements of sarcoidosis status to outcomes of interest to patients longitudinally over 6 months. Methods: Sarcoidosis patients cared for at 6 US medical centers were "phenotyped" at baseline with measurements of pulmonary function, organ involvement, health related quality of life (HRQoL) instruments, and their anti-sarcoidosis treatment history. These patients were followed for 6 months by monitoring outcomes of interest to patients (OIPs) including steps walked, calories expended, sleep, HRQoL measures, workdays missed and health care utilization. For each baseline phenotypic measurement, patients were dichotomized into two groups above and below a specified cutoff value. The area under the OIP versus time curve was compared between these two groups. Results: The cutoff values for many baseline phenotypic measures distinguished the patients into groups with significantly different 6-month OIPs. The chosen cutoff for the patient global estimate of health status distinguished the most OIPs (13/15). The 6-min walk distance cutoff was associated with more OIPs than spirometric measures. All of the HRQOL measure cutoffs were associated with many OIPs, although most of them were other HRQOL measures. Interpretation: Cutoffs for most of the phenotypic measures used to assess sarcoidosis distinguished groups of sarcoidosis patients with differing OIPs over the subsequent 6 months. The patients' global assessment of their disease was the most accurate of these measures. Clinical trial registration number: NCT04342403.